High-level meeting between the CGIAR CWANA representatives, the Minister of Agriculture, and partners INRA in Morocco - meeting minutes - Nassir, Meriem (International Center for Agricultural Research in the Dry Areas, 2022)
The meeting minutes of a high-level stakeholder engagement event in Morocco attended by His Excellency the Minister of Agriculture, Marine Fisheries, Rural Development, Water and Forestry (MAPMDREF), the CGIAR Regional Director of Central and West Asia and North Africa, the F2R-CWANA Initiative lead, the Director of INRA and members of staff from ICARDA for the purposes of reconfirming Morocco's support to the CGIAR, and the CGIAR's support to the sustainable development of agriculture in Morocco.